Uterine vascular resistance and other maternal factors associated with the risk of developing hypertension during pregnancy - Martins,L.A.B. (2021)
Gestational hypertension and pre-eclampsia are important causes of perinatal morbidity. The objective of the present study was to determine the increase in relative risk for developing hypertensive disorders of pregnancy based on the evaluation of pregnant women between 20 and 25 weeks of gestation, and to correlate the findings at this period with the outcome of pregnancy. We conducted a prospective cohort study, with a convenience sample of 1417 patients evaluated at this gestational age, of which 1306 were contacted at childbirth. We detected an increased relative risk of 2.69 (95%CI: 1.86 to 3.89) associated with pulsatility index of the uterine arteries, a 2.8 increase (95%CI: 1.58 to 5.03) in relative risk attributed to maternal age above 35 years, a 1.68 increase (95%CI: 1.17 to 2.40) attributed to parity greater than or equal to 3, and a 5.35 increase (95%CI: 4.18 to 6.85) attributed to chronic hypertension and obesity, with a progressive increase in relative risk according to the degree of overweight, i.e., grades 1, 2, 3, and morbid obesity (2.58, 3.06, 5.84, and 7.28, respectively).